VAR MODEL UNTUK ANALISIS FOREIGN DIRECT INVESTMENT DI INDONESIA - Dede Ruslan (Universitas Negeri Medan, 2014)
Vector Autoregresive model is used to gives a more comprehensive view of how the relationship of FDI to economic growth, trade, exchange rate, the output value of the industry, and the interest rate in Indonesia. This study provides empirical evidence about the relationship which are interrelated to each other among the variables analyzed. By using VAR can analyze the impact of FDI on economic growth with other variables. The empirical results of whole analysis to give an answer to the original question posed in this study relate to how economic growth has been achieved, what the role of FDI and other spillovers in this process. Through the VAR model, the interdependence between the variables FDI, GDP, Trade, Industrial Output Value, Exchange Rate and Interest rates have been investigated in long-term relationships through cointegrating vectors and the short-term impact of the VAR model. Correlation of dynamic variables have been captured by the analysis of variance decomposition and impulse response.